The benefits of using calcium score in preventing cardiac events (Research, Society and Development, 2024)
The Coronary Artery Calcium (CAC) Score is a non-invasive imaging tool that utilizes computed tomography to analyze the presence and extent of calcium in the coronary arteries. Despite some available tools to assess the population's cardiovascular risk, using CAC in conjunction with these methods makes the risk assessment outcome more accurate in some classification groups. Objective: To evaluate the use of Coronary Calcium Score in Cardiovascular Risk Stratification. Methodology: This is an integrative literature review, which used the PICO strategy and the following guiding question: "What is the prognostic relevance of calcium score in preventing acute myocardial infarction?" Results: Through the analyzed studies, it is possible to affirm that the Coronary Artery Calcium Score is an effective marker in identifying early atherosclerosis in low-risk patients, enabling early interventions. The presence of CAC is associated with a higher risk of coronary artery disease, even in young adults, while the absence of CAC is a strong marker of low risk. Performing the score is cost-effective in primary cardiovascular prevention, enabling the implementation of statins as a prophylactic intervention. Conclusion: The reviewed articles reveal how this marker can change medical behavior, influence treatment selection, and outline treatment plans tailored to the specific needs of each individual, extending also to decisions about invasive procedures.